Polymorphisms in nucleotide excision repair genes and basal cell carcinoma of the skin. (10th September 2014) - Pesz, Karolina A.; Bieniek, Andrzej; Gil, Justyna; Laczmanska, Izabela; Karpinski, Pawel; Makowska, Izabela; Trusewicz, Alicja; Sasiadek, Maria M.
Abstract Background Mutations in nucleotide excision repair (NER) genes are the cause of xeroderma pigmentosum, a genetic syndrome with proneness to basal cell carcinoma (BCC) of the skin. Single nucleotide polymorphisms (SNPs) may affect the effectiveness of DNA repair and hence influence individual susceptibility to a variety of neoplasms. The aim of this study was to find associations between SNPs in selected NER genes and sporadic BCC development. Materials and methods The study group consisted of 100 patients with histopathologically confirmed BCCs and the control group of 100 elderly individuals with no personal history of any cancer. DNA isolated from peripheral blood lymphocytes was genotyped for seven SNPs in five different NER genes. Statistical analyses for associations were performed. Results A weak association between XPD exon 6 silent C/A polymorphism and BCC development risk was found when comparing single polymorphisms between the two groups. When considering sex and SNPs, men with the A‐allele in XPC intron 11 C/A have been found to have a decreased risk of BCC. Conclusions There is no consistency in association studies between SNPs and BCC susceptibility. SNPs in NER genes seem to have an insignificant influence on the risk of developing BCC of the skin.